Analisis Surat Berharga Sebagai Alat Investasi (International Forum of Researchers and Lecturers, 2024)
This journal analyzes stocks as investment securities. In the modern era, stocks have become a popular investment choice due to their high potential returns and ease of access through digital platforms. However, stock investments also carry significant risks, such as sharp price fluctuations. This study aims to provide a deeper understanding of the advantages of stocks compared to other investment instruments, factors influencing public interest in stock investments, and the development of stock investments in Indonesia after the enactment of Law No. 11 of 2020 on Job Creation. The research method used is normative and juridical approaches, by examining legislation and related literature. The expected outcome of this study is to enhance financial literacy among the public and assist in making smarter and wiser investment decisions.